2013
DOI: 10.1074/jbc.m112.416297
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Cyclin-dependent Kinase Inhibitor 1A Gene (CDKN1A) by the Repressor BOZF1 through Inhibition of p53 Acetylation and Transcription Factor Sp1 Binding

Abstract: Background:The POK proteins play roles in the regulation of the cell cycle, oncogenesis, and tumor suppression. A novel POK protein, BOZF1, is overexpressed in cancer. Results: BOZF1 represses transcription of CDKN1A by inhibition of p53 acetylation and Sp1 binding. Conclusion: BOZF1 stimulates cell proliferation by repressing p21 expression. Significance: BOZF1 is a negative regulator of tumor suppressors p53 and p21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…The transcription factors p53 and Sp1 regulate various cell functions, including the promotion of apoptosis, suppression of cell growth, migration, and invasion [ 25 , 26 , 27 ]. To further investigate the underlying molecular mechanisms of CH-5-mediated anticancer activities, the expression level of p53 and Sp1 proteins was examined in U2OS cells treated with CH-5, using Western blotting analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription factors p53 and Sp1 regulate various cell functions, including the promotion of apoptosis, suppression of cell growth, migration, and invasion [ 25 , 26 , 27 ]. To further investigate the underlying molecular mechanisms of CH-5-mediated anticancer activities, the expression level of p53 and Sp1 proteins was examined in U2OS cells treated with CH-5, using Western blotting analysis.…”
Section: Resultsmentioning
confidence: 99%
“…HKR3 Potently Activates Transcription of the ARF Gene-Recently, we found that some POK proteins regulate the cell cycle by controlling the p53 pathway (1)(2)(3)(4)(5). Accordingly, we investigated whether HKR3 inhibited cell proliferation by controlling expression of genes within the ARF-p53 pathway.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…POK family proteins, such as ZBTB2, ZBTB5, ZBTB7A(FBI-1), ZBTB7C(KR-POK), and ZBTB8A(BOZF1), were shown to regulate cell cycle and proliferation through the regulation of CDKN1A, a gene member of the p53 pathway (ARF-MDM2-TP53-CDKN1A). CDKN1A encodes the protein p21, which is a negative regulator of the cell cycle (1)(2)(3)(4)(5). In particular, interactions between certain POK family proteins and co-regulators (e.g.…”
mentioning
confidence: 99%
“…ZNF509L activated transcription of CDKN1A , by binding to its promoter proximal GC boxes and interacting with both MIZ-1 and the co-activator p300 (Figure 8 ) to induce CDKN1A transcription. These proximal GC boxes are the target sites for not only transcription factors like Sp1 but also several other POK family members previously reported as proto-oncoproteins ( 16 , 18 , 30 , 40 , 46 ). Also, oncoproteins that lack direct DNA binding activity to the CDKN1A promoter, including MYC, BCL6 and GFI-1, interact with MIZ-1 to gain promoter access and repress CDKN1A ( 6 , 11 , 13 ).…”
Section: Discussionmentioning
confidence: 99%